Introduing the religious wisdom for sustainble built environment - Ahmed Shogar, Ibrahim Adam (2012)
The modern scientific and technological culture has made man to realize the importance of ecological equilibrium and environmental health to his life. Sustainable built environment is the idea which allows maintaining and extending quality of life through the various generations. In fact, the dawn of environmental and ecological consciousness is arising throughout the global community. Man equipped by green technologies can develop a peaceful built environment and great paradise on earth. The strategic method to create such environment is to introduce the religious wisdom as foundation to articulate the growing consciousness on sustainable interaction with nature. The main objective of this paper is to examine the hypothesis that the religious wisdom is central in ecological and environmental consciousness. The paper also emphasizes the notion that science and technology are main sources of sustainable development of human community. It notes that the growing consciousness on environmental matter figures the importance of the religious worldview for long term recovery of environmental crisis.